Increasing Teenagers' Knowledge About Whiteness Through Media Games Flash Cards And Leaflets - Putri, Shalsabilillah Defia; Dewi, Ratna; Septiyanti (Poltekkes Kemenkes Bengkulu, 2024)
Problems with female reproductive organs have reached 33% of the total burden of disease in women throughout the world, one of which is fluor albus. Most teenagers who have experienced vaginal discharge still do not know about vaginal discharge, and almost all young women often do not receive information about how to prevent vaginal discharge. This is very dangerous, because improperly maintaining the cleanliness of the reproductive organs will make vaginal discharge worse. The aim of this research is to determine the effectiveness of health education through flash card games and leaflets on knowledge about vaginal discharge in young women. This research is researchquasi experimental designs with the nonequivalent control group design approach. The sample for this research was 48 SPMN 2 Bengkulu City students who were divided into 2 groups and taken using a systematic random sampling technique. Data were collected using questionnaires in the intervention group and control group. The research results were analyzed univariately and bivariately. The research results showed that there was an increase in knowledge about vaginal discharge in teenagers after health education was carried out through flash card games and leaflet media. The results of the analysis show that health education through flash card games media is more effective than leaflet media in increasing knowledge about vaginal discharge in young women. It is hoped that health education for teenagers using flash card games as a media can increase the activity of the participants so that they will achieve the expected activity goals. Keywords: Health Education, Vaginal Discharge, Knowledge.